Mistakes made in the process of filling in the complaint form of the European Court of Human Rights - Gelantia, Lasha (COLLECTION OF SCIENTIFIC WORKS OF SOKHUMI UNIVERSITY, 2023)
The European Court of Human Rights is an international court whose judgments are binding on states and cause governments to change their laws and administrative practices in many areas. The court may also hear complaints from individuals and legal entities alleging that their human rights under the Convention have been violated.Practice has shown that more than 90% of the complaints reviewed by the court are declared inadmissible, which is often caused by errors made in the process of filling out the complaint form developed by the court.The topic discusses typical and common mistakes, such as: improper use of the complaint form, incorrect indication of factual circumstances, no annexes are attached properly, Exhaustion of domestic defense mechanisms is not rationaled, lack of signatures, inconsistency of the page etc.The topic also includes practical advice-recommendations to achieve the desired result in the European Court of Human Rights.